2001
DOI: 10.1002/1099-0690(200112)2001:23<4423::aid-ejoc4423>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of Medium-Sized Ring-Bridged Oxabicycles by Ring-Closing Metathesis

Abstract: A flexible strategy is described for the enantioselective construction of both optical antipodes of the oxabicyclo[4.2.1]-, -[5.2.1]-, and -[6.2.1]alkenes by a ring-closing metathesis [a] Instituto de Productos Naturales y Agrobiología, CSIC,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The second‐generation Grubbs catalyst16 ( 23 , Scheme ) was employed but did not provide the RCM adducts, even not under microwave conditions. Other authors have described similar difficulties in the preparation of similar or even less sterically demanding polycyclic compounds 17…”
Section: Resultsmentioning
confidence: 81%
“…The second‐generation Grubbs catalyst16 ( 23 , Scheme ) was employed but did not provide the RCM adducts, even not under microwave conditions. Other authors have described similar difficulties in the preparation of similar or even less sterically demanding polycyclic compounds 17…”
Section: Resultsmentioning
confidence: 81%
“…As mentioned in the introduction, the assembly of medium‐sized carbocycles by ring‐closing metathesis (RCM) requires the precursors to be somewhat pre‐organized so that the entropic cost of the process is not too high. The groups of Hanna,14 Armas and García Tellado,15 and Tadano16 independently demonstrated that it is possible to make oxa‐bridged eight‐membered carbocyclic systems by RCM of dienyl precursors containing a suitable 1,5‐oxygen bridge (Scheme 5). Using this strategy Tadano and co‐workers prepared the core of Mycoepoxydiene, a fungal metabolite isolated from the fermentation of a fungus in 1999 (Scheme 5c).…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used with varying degrees of success on a broad range of substrates to overcome the challenges of medium ring and macrocycle formation . In particular, substrates related to the bis‐alkene 1 , such as a cyclohexane‐fused precursor ( 3 ) and a tetrahydrofuran diol with an anti ‐configuration ( 4 ) have been reported to cyclise in good yields (Scheme ). However, a substrate with no 3,4‐substitution of the tetrahydrofuran ( 5 ) failed to cyclise, highlighting how a nine‐membered ring closure can be very sensitive to changes in substrate structure.…”
Section: Introductionmentioning
confidence: 99%